2021
DOI: 10.21037/jgo-21-61
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the ratio of carcinoembryonic antigen concentration to maximum tumor diameter in patients with stage II colorectal cancer

Abstract: Background: Recently, a study from our center indicated that the ratio of preoperative carcinoembryonic antigen (CEA) concentration to maximum tumor diameter (DMAX) may be a prognostic marker for patients with rectal cancer. Therefore, the study aimed to evaluate whether this ratio (CEA/DMAX) has prognostic value for patients with stage II colorectal cancer (CRC). Methods: A prospectively maintained database was searched for patients with pathologically confirmed stage II CRC who underwent surgery between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Tumor-node-metastasis (TNM) staging is considered the most robust predictor of outcomes and the primary guidance for the subsequent therapy of patients with CRC. Stage II CRC accounts for approximately 25% of all CRC cases (3), and approximately 15-25% of patients relapse or die within 5 years of radical surgery (4). For primary curative CRC, adjuvant chemotherapy is inappropriate for stage I patients and considered the standard treatment for stage III patients under the National Comprehensive Cancer Network guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-node-metastasis (TNM) staging is considered the most robust predictor of outcomes and the primary guidance for the subsequent therapy of patients with CRC. Stage II CRC accounts for approximately 25% of all CRC cases (3), and approximately 15-25% of patients relapse or die within 5 years of radical surgery (4). For primary curative CRC, adjuvant chemotherapy is inappropriate for stage I patients and considered the standard treatment for stage III patients under the National Comprehensive Cancer Network guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies revealed that serum CEA correlates to various confounding factors such as age, smoking, and tumor diameter ( 34 , 35 ). Li et al and Cai et al identified that the CEA/tumor diameter (measured on postoperative specimens) is a more reliable predictor of DFS and OS in patients with CRC ( 23 , 24 ). In our study, we confirmed that patients with high CEA/Dia path encounter unfavorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been firmly established as an independent predictor for treatment response and postoperative survival in diverse malignant tumors, such as gastric cancer, non-small cell lung cancer, and CRC ( 19 - 22 ). Considering the robust positive correlation between serum CEA and tumor size, two studies revealed that the CEA/tumor diameter as an independent prognostic factor was superior to CEA in predicting postoperative recurrence and death in CRC ( 23 , 24 ). Unlike tumor diameter which solely refers to the longest distance across single-section, tumor volume encompasses the entirety of the tumor space, regardless of shape ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies on CEA levels, the positive rate was relatively low ( 19 ), and although patients with a normal range of CEA also had prognostic significance based on reduced cutoff points ( 35 , 36 ), the sensitivity was relatively low (46.00%) ( 37 ) with a limited AUC in predicting survival that ranged from 0.636 (cutoff, 11 µg/ml) ( 38 ) and 0.645 (cutoff, 5 µg/ml) ( 39 ) to 0.740 (cutoff, 12.5 µg/ml) ( 40 ). A recent study indicated that the CEA to maximum tumor diameter ratio has prognostic value; however, the AUC of the new marker in predicting 3-year OS was reported to be only 0.704 ( 41 ). For BMI, its application in prognosis was largely blocked by inconsistent criteria and conflicting results, as aforementioned ( 10 – 14 ).…”
Section: Discussionmentioning
confidence: 99%